Relationship of Situational Leadership Style of Principal and School Climate to Teacher Integrity PAUD at Gambir Sub-District Central Jakarta - Wanto Wanto (Ilomata International Journal of Social Science, 2021)
The purpose of this study is to findout the relationship between the principal's situational leadership style and the school climate together with the integrity of paud teachers in Gambir Sub-District of Central Jakarta. This research includes a type of quantitative research with koresional techniques. The population in this study is all paud teachers in Gambir Sub-District of Central Jakarta which numbered 63 people. The sample from this study is the entire population. Data collection techniques use questionnaire methods and documentation. The research data in the analysis of two forms is descriptive and inference analasis. Description analysis is performed in the form of basic statistics such as average, median mode, standard deviation, variance, total score of distribution tables and histograms. Inference analysis consists of prerequisite analysis and hypothesis test. The conclusion of this study is that thereis a positive relationship between situational leadership style and schooliklin together with paud teacher integrity in Gambir Sub-district of Central Jakarta with double correlation coefficient (r12y)of 0.1509 and coefficient of determination of 0.388. This points out that if the situational leadership style and the school climate are jointly improved then the integrity of teachers is improved through the regression equation = 87.8+0.26 b1+0.02b2. This means the better the principal's leadership style and school climate the better the integrity of the teacher.